2020
DOI: 10.1021/acs.macromol.0c00318
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation of Ionic Liquid-Containing Diblock Copolymers: Effects of Dielectric Inhomogeneity and Asymmetry in the Molecular Volumes and Interactions between the Cation and Anion

Abstract: We study the phase behavior of a block copolymer and ionic liquid mixture using the Landau theory of Leibler and field-theoretic techniques in polymer physics. Our weak-segregation theory of microphase separation accounts for electrostatic screening, the excluded volume effect, and the dielectric contrast between the species. The results of the phase diagrams for ionic liquid-containing poly­(styrene-block-2-vinylpyridine) and poly­(ethylene oxide-block-styrene) qualitatively agree with the observed transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…They therefore suggested that the dielectric mismatch is the main reason for the drastic change in the phase diagram. In summary, factors including ion solvation energy, , , ion translational entropy, ,,, ion correlation, transient binding, ,, and asymmetry in the molecular volumes between cations and anions have been shown theoretically to impact the thermodynamics of ion-containing polymer systems. Although there is no agreement on which specific factor(s) leads to the change in the phase behavior of such ion-containing blends and copolymers, a well-accepted result is a quite asymmetric phase diagram with decreased compatibility when the charged (or salt-doped) component is in the minority.…”
Section: Resultsmentioning
confidence: 99%
“…They therefore suggested that the dielectric mismatch is the main reason for the drastic change in the phase diagram. In summary, factors including ion solvation energy, , , ion translational entropy, ,,, ion correlation, transient binding, ,, and asymmetry in the molecular volumes between cations and anions have been shown theoretically to impact the thermodynamics of ion-containing polymer systems. Although there is no agreement on which specific factor(s) leads to the change in the phase behavior of such ion-containing blends and copolymers, a well-accepted result is a quite asymmetric phase diagram with decreased compatibility when the charged (or salt-doped) component is in the minority.…”
Section: Resultsmentioning
confidence: 99%
“…At r = 1/200–1/50, Li + ions show higher selectivity toward the PEO block, so that LiCl is mainly located in the PEO domains. Since the dielectric constant of PEO (7.5) is higher than that of P4VP (3.5), [ 68 ] Δ χ Born is larger than 0. Moreover, one Li + ion can complex with multiple O atoms, but the complexation strength is weak, as evidenced by the high mobility of Li + ions in PEO/Li + solid polyelectrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of the simplification of ILs could also be somewhat anticipated because, despite the structural and chemical diversity of ILs, the Walden rule for electrolytes takes a very simple form, (molar conductivity) × (viscosity) = temperature‐dependent constant, yet the formula applies to a broad spectrum of ILs 65 . Moreover, in Reference 66, the weak‐segregation theory of Leibler with the Born solvation energy of the ions also accounted for the phase boundaries of the microphase separation of IL‐containing diblock copolymer observed by Virgilli et al 53 and Simone and Lodge, 67 treating the ions as charged spheres with the excluded volume and dielectric constant. Thus, it appears to be possible to depart from simplified models for ILs in dielectric continuums and consider a mixture of polymer and IL.…”
Section: Introductionmentioning
confidence: 99%